2017
DOI: 10.1016/j.drugalcdep.2017.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Social contextual risk factors for stimulant use among adolescent American Indians

Abstract: Objective Stimulants are the most common and efficacious treatment for Attention-Deficit Hyperactivity Disorder (ADHD). We examined the relationship between stimulant misuse and social factors that could be malleable to prevention among American Indian (AI) adolescents. Method Participants were AI students (N=3,498) sampled from 33 schools in 11 states. Participants completed the American Drug and Alcohol Survey. A multilevel analytic approach was used to evaluate the effects of participant-level (level 1) v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…Individual study details are available in Table S1, available online. 9,11,15,[18][19][20][21][22]27,31,32,[42][43][44]50,52,54,55,58,61,63,[72][73][74][75][76][77]80,82,84,93,[95][96][97][98][99][100]103,105,109,118 NMU ¼ nonmedical use.…”
Section: Figure 2 Percentages Of Individuals Who Self-reported Nonmedmentioning
confidence: 99%
“…Individual study details are available in Table S1, available online. 9,11,15,[18][19][20][21][22]27,31,32,[42][43][44]50,52,54,55,58,61,63,[72][73][74][75][76][77]80,82,84,93,[95][96][97][98][99][100]103,105,109,118 NMU ¼ nonmedical use.…”
Section: Figure 2 Percentages Of Individuals Who Self-reported Nonmedmentioning
confidence: 99%
“…Parental monitoring. Past research has indicated that weak monitoring of adolescents' behavior by parents is related to increased risk of stimulant use (Spillane et al, 2017), necessitating the inclusion of this variable in analyses. Parental monitoring was measured using a series of four ordinal items assessing the degree to which participants report that their parents monitor their behavior, with higher scores indicating greater monitoring (e.g., How often do you have a set time to be home on weekend nights?).…”
Section: Socioeconomic Status (Ses)mentioning
confidence: 99%
“…Social control mechanisms posited by Hirschi (1969) have been identified as risk factors for stimulant use. Weakened social control in the forms of low religiosity, weak parental monitoring, and low commitment to school have all been identified as risk factors for stimulant use (Herman-Stahl, Krebs, Kroutil, & Heller, 2007; McCabe, Knight, Teter, & Wechsler, 2005; Spillane, Weyandt, Oster, & Treloar, 2017). Social control theory (Hirschi, 1969) would predict that this is due to the weakened bond that an individual has to conventional society, freeing them to engage in deviant behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies on tobacco use among AI adolescents have tended to focus on isolated regions or tribes, though there is reason to believe that rates may differ by region based on previous substance use research examining stimulant (Spillane, Weyandt, Oster, & Treloar, 2017) and alcohol use (Whitbeck et al, 2014). Spear and colleagues (2005) examined lifetime and past month cigarette use among 7 th grades from the Northern Plains and found higher rates of smoking among American Indians, compared to White students (Spear, Longshore, McCaffrey, & Ellickson, 2005).…”
Section: Introductionmentioning
confidence: 99%